Legal framework of central-local government administrative relationship and Its implication on the autonomy of local government authorities in Mainland Tanzania - Mnyasenga, Thobias, R. (Mzumbe University, 2023)
A Thesis Submitted in Fulfilment of the Requirements for the Degree of Doctor of Philosophy of Mzumbe University 2017